Co-torrefaction of pine needles and pine cones: Synergistic effects on fuel properties and energy density - Kardas, Elif; Nafra, Ahmad; Tasar, Seyda; Yilgin, Melek (Wiley, 2026)
Biomass residues such as pine needles and pine cones, which accumulate in large quantities in forest ecosystems, can be converted into valuable solid biofuels through thermochemical conversion technologies. In this study, the co-torrefaction behavior of pine needles (PN), pine cones (PC), and their blends at different mixing ratios was investigated, and the effects of blend interactions on solid product yield and fuel properties were evaluated. Torrefaction experiments were conducted at 200, 250, and 300 degrees C for 60 min under an inert atmosphere. Raw and torrefied samples were characterized by proximate and elemental analyses, higher heating value (HHV), FTIR, and thermogravimetric analysis (TGA). The results showed that increasing torrefaction temperature significantly enhanced fuel properties. The HHV increased from 18.99-20.83 MJ/kg for the raw materials to 25.16-26.29 MJ/kg at 300 degrees C, while the H/C and O/C atomic ratios decreased from 1.58-1.80 and 0.60-0.71 to 0.80-0.93 and 0.32-0.37, respectively. Pine cones exhibited higher solid product yields under severe torrefaction conditions, reaching 57.40%, compared with 48.52% for pine needles, owing to their higher lignin content and thermal stability. Comparison of the calculated expected solid product yields (EV) with the experimental yields of the blends revealed synergistic interactions during co-torrefaction. TGA results confirmed the improved thermal stability of torrefied samples and significant changes in biomass decomposition behavior following thermal pretreatment. These findings demonstrate that co-torrefaction of pine needles and pine cones is an effective strategy for upgrading forest residues into energy-dense solid biofuels and highlight the potential of such blends as renewable energy resources.
Keywords: Co-Torrefaction; Energy Density; Forest Biomass Residues; Fuel Upgrading; Pine Needle-Pine Cone Blends; Synergistic Interactions; Torrefied Biofuel